Pengembangan multimedia pembelajaran untuk meningkatkan hasil belajar kognitif materi sistem respirasi - Din Hadi Shofyan; Siti Zubaidah; Amy Tenzer (Universitas Negeri Malang, 2021)
Observations in MAN Malang II Batu and giving questionnaires to a number of students shows that students still have difficulty understanding abstract concepts on the material of the respiratory system. It can also be seen from the thoroughness of classical study that has not been achieved. The use of instructional media is still minimal and less attractive to students, believed to be a major factor to the achievement of mastery learning klasial. To that end, the development of multimedia learning based on flash needs to be done on the grounds can create a variety of interesting and illustrative media. With the learning multimedia is expected to facilitate students in understanding the abstract concepts of matter respiratory system and learning becomes fun. Penelitian dan pengembangan ini bertujuan untuk mengembangkan multimedia pembelajaran berbasis flash untuk meningkatkan hasil belajar kognitif siswa materi sistem respirasi manusia serta menguji kelayakan, kepraktisan dan keefektifannya. Model pengembangan menggunakan Four-D model yang dibatasi sampai tahap III (pengembangan). Hasil uji kelayakan, kepraktisan dan keefektifan menunjukkan bahwa multimedia yang dikembangkan memiliki kriteria sangat layak, sangat praktis, serta efektif. Dapat disimpulkan bahwa multimedia pembelajaran berbasis flash memiliki kriteria sangat layak, sangat praktis dan efektif sehingga mampu meningkatkan hasil belajar kognitif siswa.